STUDI BANDING PEMANFAATAN SISTEM INFORMASI GEOGRAFIS UNTUK PROFIL KECAMATAN DAN PERENCANAAN WILAYAH DESA: PENDEKATAN DALAM MENDUKUNG PERENCANAAN PEMBANGUNAN BERBASIS SPASIAL - Tamba, Hotler; Lubis, Ruri Prihatini; Hidayat, Wahyu (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2025)
Geographic Information Systems (GIS) have become a crucial technology in spatial planning and development, particularly for managing complex spatial and attribute data. This study aims to compare two applications of GIS at different scales: first, the use of GIS to create spatially-based regional profiles in Sukolilo District, and second, the application of GIS to map village facilities in Dusun Godhean, Kucur Village. The first study emphasizes the integration of spatial data, such as demographics, geography, and public facilities, to support district-level development planning. Meanwhile, the second study focuses on managing local village data, such as residential areas, village facilities, and residents’ economic conditions, to enhance the efficiency of data management and decision-making at the village level. A descriptive-comparative approach was employed to analyze the benefits, challenges, and opportunities of both GIS implementations. The data were analyzed based on methods, geographic coverage, data relevance, and their impact on spatial planning. The findings show that GIS at the district level provides broad and integrated spatial insights to support strategic development policies. On the other hand, GIS at the village level is more specific in mapping local facilities, aiding the efficient management of local areas. Both approaches face challenges such as limited access to high-resolution data, the need for advanced technology, and the availability of skilled human resources. This study recommends integrating the two approaches to create a more holistic GIS system. District-level GIS can be utilized for strategic analysis, while village-level GIS can enrich detailed local data to support micro-level planning. This integration is expected to enhance the efficiency of spatial-based planning at local and regional levels, thereby supporting more inclusive, adaptive, and sustainable development.